Recidivism among forensic psychiatric patients undergoing outpatient treatment for mental health disorders – A meta-analysis - Bali, Panagiota; Chatzinikolaou, Fotios; Karachaliou, Evangelia; Lickiewicz, Jakub; Lantta, Tella; Tasios, Konstantinos; Efstathiou, Vasiliki; Douzenis, Athanasios (Pergamon Press, 2026)
Introduction
The risk for general or criminal recidivism in forensic psychiatric patients has not been extensively investigated in the literature. The aim of this review is to evaluate criminal recidivism among forensic patients with mental disorders undergoing some type of outpatient treatment.
Methods
In this review, we utilized PubMed, Embase, Scopus, and the Cochrane Library to search for studies published from January 1990 up to July 2024. Eligible studies should i) evaluate forensic patients with mental health conditions, ii) evaluate patients undergoing outpatient treatment, and iii) evaluate criminal recidivism (general, sexual, or violent) as a primary outcome. Recidivism was also compared between groups when reported.
Results
Overall, 12 clinical studies including 3271 patients were evaluated. Of these, 3048 patients undergoing outpatient treatment were analyzed. The mean age of all patients was 23.4 years (SD = 6.3), and 79.7 %. were male. The mean follow-up was 33.82 months. Overall, the pooled proportion for general recidivism was 39.1 % (95 % CI: 25 %–54.3 %), and for violent recidivism was 21.7 % (95 % CI: 2.6 %–52.3 %; data from four studies). In group comparisons (data from five studies), there was no difference between patients under treatment and the control groups as far as general recidivism (OR = 0.489; 95 % CI [0.202–1.183]; P = 0.112), and violent recidivism (OR = 0.283; 95 % CI [0.056–1.416]; P = 0.124) were concerned.
Conclusion
The general and violent recidivism rates are high among forensic patients undergoing outpatient treatment for mental health disorders. There was no difference between outpatient treatment and control groups regarding their effect on recidivism. However, most of the studies reviewed did not provide information about drug treatment; more comparative studies focusing on pharmacotherapy are needed to verify any benefits of outpatient treatment.